The Evolution of Information Management Models in Enterprises and the Proposal of the 4F-DIM model - Olga OKRZESIK (Communications of International Proceedings, 2025)
Today's organizations operate in an environment of intensive digitalization, where information is not only an operational resource, but a strategic asset that drives innovation, competitive advantage, and adaptability. The aim of the paper is to analyze the evolution of information management models in the context of the digital transformation of the enterprises and to propose new universal model. A review of the literature points to the growing importance of hybrid models and the need for technological integration, data management, and an adaptive organizational approach. Traditional and emerging enterprise information management models differ primarily in their approach to control and automation, with traditional models focusing on hierarchical compliance and emerging models emphasizing agile, decentralized technology integration. This article presents the 4F-DIM model (Four Pillars of Digital Information Management) – an original conceptual proposal that systematizes the key dimensions of information management in the digital era. It was developed as a response to an identified gap in the integration of data, technology, decision-making and organizational structure management. This model is based on four pillars: technological foundations, data functions, forms of coordination and decision pillars (strategy and value). The model can provide a framework for further research and implementation in the context of digital transformation of enterprises.
Keywords: information management; digital transformation; hybrid models; data management; 4F-DIM model